“Optimization of Shaft Dimensions: A Comparative Study Using Computational Method and Finite Element Analysis” - Vinod N. Patni (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study presents a novel approach to optimizing shaft dimensions, essential for efficient torque transmission in mechanical systems. Traditionally, conservative estimates lead to oversized shafts, compromising material efficiency. We developed a computational method using C programming to precisely calculate optimal dimensions for both solid and hollow shafts. The results were validated against manual calculations and finite element analysis (FEA) performed with Radioss software from Altair. Additionally, Pro-Engineer software was used for further verification. Our method demonstrated high accuracy and alignment with traditional and FEA results, providing a reliable solution for precise shaft design. This approach significantly enhances material efficiency and mechanical performance, offering a streamlined and effective tool for engineers in the field.